2019
DOI: 10.1002/tea.21587
|View full text |Cite
|
Sign up to set email alerts
|

“I just do what the boys tell me”: Exploring small group student interactions in an integrated STEM unit

Abstract: Gender equity issues remain a challenge in science, technology, engineering, and mathematics (STEM) fields, where women are highly underrepresented. As integrated STEM instruction becomes increasingly popular in elementary and middle school classrooms, it is important to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 81 publications
(106 reference statements)
2
38
0
1
Order By: Relevance
“…This situation leads to even fewer opportunities to gain experience and increase their confidence with computers, which can be observed among girls as well as among less experienced boys. When students, whether girls or boys, fall into this vicious circle (Wieselmann et al 2020), it is not very likely they escape it without the explicit initiative of the school and parents who would create an engaging environment effectively pulling these kids back in CS education. As girls fall in this vicious circle more often than boys, it is natural to ask, what the girl-friendly CS education environment looks like, what requirements it poses on the curriculum, culture, and the overall environment (RQ3).…”
Section: Effective Measures and Strategiesmentioning
confidence: 99%
“…This situation leads to even fewer opportunities to gain experience and increase their confidence with computers, which can be observed among girls as well as among less experienced boys. When students, whether girls or boys, fall into this vicious circle (Wieselmann et al 2020), it is not very likely they escape it without the explicit initiative of the school and parents who would create an engaging environment effectively pulling these kids back in CS education. As girls fall in this vicious circle more often than boys, it is natural to ask, what the girl-friendly CS education environment looks like, what requirements it poses on the curriculum, culture, and the overall environment (RQ3).…”
Section: Effective Measures and Strategiesmentioning
confidence: 99%
“…In addition, researchers used a coding protocol based on Jovanovic and King's [65] protocol that examined student participation in small group science activities. The science-focused protocol was modified and expanded upon to include performance enactments of integrated STEM and engineering activities [98]. The final coding protocol consisted of 33 performance enactments, including both verbal and non-verbal means of participation (see Appendix A).…”
Section: Discussionmentioning
confidence: 99%
“…We know from prior research that development of an engineering identity is critical in supporting and encouraging youth participation in future engineering experiences [5], [7] and so focusing on questions around how and in what ways early engineering identity forms is critical. We know from previous research that girls and boys experience engineering in different ways [3], [22], but don't yet understand what specific aspects of the learning environment might be affecting these gendered ways of participating and how those might affect engineering identity development. As early as elementary school, we see gender differences in participation [16] which suggests a need for attention to practices and experiences which promote equity in engineering participation and identity development.…”
Section: Discussionmentioning
confidence: 99%
“…Moote et al [15] found genderlinked disparities in career aspirations in engineering, positing that this disparity shows how the traditional branding of engineering as masculine is still greatly affecting students' relationships to engineering. Some studies have found instances of gatekeeping in engineering, where young boys try to assert that engineering is not a female space, taking control of projects and not collaborating with female group members [3], [15]. Girls must navigate difficult-to-access, traditionally male spaces, and reconcile performance of engineering and feminine identities, which are considered socially incompatible, in order to construct an engineering identity [15].…”
Section: A Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation